IMPLEMENTASI PENDIDIKAN KARAKTER DALAM PERKULIAHAN - Nailariza Umami (JPEKBM (Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis dan Manajemen), 2018)
Mentality is related to ways of thinking that have become habits, or habits of thought. And a habit, generally formed through habituation. Therefore mentality can be formed, by way of habituation and coaching. Efforts to refract and guide need to touch two factors at once: ways of thinking and the environment. And the educational environment is one way out to foster the character of the younger generation in a directed, programmed, and optimal way so that young people who are intelligent intellectual and moral quality can be formed. Planting character values that are integrated in lectures can be expected to be internalized in students. The courses taught are not just theoretical knowledge, but can also be shown in the form of behavior in preparation for The research steps are plan, action, observation, and reflection. The research subjects were students in the 4th semester Learning Planning lectures in the STKIP PGRI Tulungagung economic education department. The method of implementation is(1) conveying character values when delivering learning planning as a basis for completing tasks; (2) delivery of values associated with the content of learning planning material; and (3) monitoring internalization of values through interviews and weekly task consultations, assessment points include indicator hard work points in the form of consultative discipline and task quality, indicator collaboration points in the form of division of roles, communication, interactions, and initiatives in study groups. The results of the character education implementation study showed an increase towards the good behavior of students and able to improve student achievement. Learning achievement is considered as a side effect of character education in the learning process.